Effect of Biomass Fly Ash on Fresh and Hardened Properties of High Volume Fly Ash Mortars - Teixeira, Elisabete R. (2021)
The objective of this work was to assess the use of biomass fly ash (BFA) as cement replacement material or as an alkalinity source in high volume fly ash mortar and concrete. Mortar formulations were prepared with different types of cement replacement: fly ash from thermal power plants, BFA, a blend of two pozzolans, and small amounts of BFA or/and hydrated lime (HL). Mortar formulations were tested both in the fresh and hardened state. The replacement of cement by the two fly ashes led to a decrease in the mechanical strength. The best strength values were obtained when higher HL content was introduced in mortars, however, mortars with the lower BFA content presented the best results for the majority of the tests. In general, BFA has a similar effect on cementitious mortars to coal fly ash, having good performance as cement replacement.